Analysis of the Isothermal Elastohydronamic Lubrication of Inclined Double-roller Enveloping Hourglass Worm Drive - Li Jinkuan; Liu Zaixin; Zhang Cui; Zhu Yan (Jixie chuandong)
To improve the lubrication performance,antiscuffing capacity and efficiency of worm gear pairs drive,the isothermal elastohydrodynamic lubrication（ EHL） simplified model and isothermal line contact mathematical model are established based on meshing theory of inclined double-roller enveloping hourglass worm drive and the theory of EHL. The oil film pressure and thickness curves are got by using Newton iteration and Newton-Raphson method. At the same time,the EHL characters on dedendum circle,reference circle,addendum circle of worm gear and every contact lines are analyzed,and the influence of lubricating oil viscidity on EHL characters of the inclined double-roller enveloping hourglass worm drive is analyzed at last. The result shows that this worm drive has better lubrication performance,the EHL characters from reference circle to addendum circle are better than other area. The oil film thickness of contact line 4 is bigger than other contact lines,the second peak pressure is smaller. The greater viscidity,the lubrication characters is better.